ANALISIS FAKTOR PEMBENTUK TINGKAT KESEHATAN BANK PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
The purpose of this study aims to determine the main factor that shape the health of banks in the banking industry in Indonesia based on the ratio CAMELS. Population in this study is the entire banking industry are listed on a stock exchange Indonesia during 2010-2013. The sampling technique used in this study using purposive sampling method with the criteria listed for 4 years in a row. The total number of samples in this study were 29 bank. However, there were 3 samples were classified as outliers and should be abolished and the number of samples become 26 samples. Data used for this study is financial ratio that according to CAMELS ratio, consisting of CAR(Capital Adequacy Ratio) and PER (Price Earning Share) as Capital aspects, APB (Aktiva Produktif Bermasalah) and NPL (Non Performing Loan) as Assets aspects, PDN as Management aspects, ROE (Return On Equity) and NIM (Net Interest Margin) as Earning aspect, LDR (Loan To Deposit Ratio) as Liquidity aspects, and Sensitivity as Sensitivity to market risk aspect. Techniques of analysis in this study is using factor analysis. The analysis showed that from 9 ratio, there are 4 of them are the permanent factors that forming the banks performance. That four ratio is PER (Price Earnings Ratio), NPL (Non Performing Loan), PDN (Posisi Devisa Netto) and NIM (Net Interest Margins).Keywords: The Health of Banking, CAMELS , Principle Factors